Finance as 'bizarre bazaar': Using documents as a source of ethnographic knowledge. (July 2019) - Tischer, Daniel; Maurer, Bill; Leaver, Adam
Markets and finance have long attracted ethnographic interest but the nature of their activity – opaque, secretive and increasingly placeless – precludes traditional ethnographic fieldwork. In this article, we propose documents as an alternative access point to these organisations as an ethnographic object of enquiry. Documents do not only present a written record, but they also enact relationships and encode tacit understandings. We develop Geertz's work on the bazaar by taking an indirect route to access the field site – collateralised debt obligation – through documents. In reading these documents, we assume the position of investors who, in the absence of alternative publicly available information, are dependent on the documentary accounts made available to them by the sellers. These media act in ways that are similar to tourist guidebooks, a comparison we use to reframe the exchange as one that builds upon sociocultural relations rather than the abstract market relationships described by mainstream economists. We propose that these documents are not merely representational artefacts of the organisation but serve to establish and maintain social relationships between buyers and sellers through the management, standardisation and ritualisation of information disclosed to the investor.